Theoretical study of hydrazine adsorption on Pt(111): Anti or cis? - Agusta, Mohammad Kemal (Animo Repository, 2011)
Hydrazine (N2H4) adsorption on metal surface is important due to its application in the direct hydrazine fuel cell technology. First principles DFT calculations have been carried out to understand the structure and mechanism of hydrazine adsorption on Pt(111). Calculations revealed that configuration with hydrazine adsorbed on its anti-conformation yields the largest adsorption energy suggesting it to be the most stable structure on Pt(111). This result was found to be in disagreement with available XPS results which favor the adsorption on cis-conformation as the most stable configuration. However, by taking into account the energy cost for orbital re-hybridization and internal rotation involves in the adsorption, it was found that the interaction strength between adsorbate and substrate is comparably equal for adsorption on both anti and cis-conformations that indicates the feasibility of the adsorption in cis-conformation to occur. Charge transfers from lone-pair orbitals belong to the highest occupied molecular orbital (HOMO) and second highest occupied molecular orbital (S-HOMO) were found to be important in the formation of the bonding. The π-anti-bonding HOMO lone-pair transfers its charge to the surface which stabilizes the internal structure of the molecule and responsible for the stable anti-conformation adsorption structure. The interaction of the π-bonding S-HOMO lone pair with the surface was found to be dative type and plays an important role in the stabilization of cis-conformation adsorption structure. © 2011 Elsevier B.V. All rights reserved.